Prognosis associated with redo cardiac resynchronization therapy following complete device and lead extraction due to device-related infection. Issue 5 (6th April 2017) - Seifert, Martin; Moeller, Viviane; Arya, Anita; Schau, Thomas; Hoelschermann, Frank; Butter, Christian
Abstract: Aims: An increase in the number of cardiac resynchronization therapy (CRT) device implantations worldwide has led to a consequent increase in the number of infections associated with the device, making extraction of the CRT device inevitable. Redo CRT implantation after treatment and recovery following device extraction is challenging. This study aimed to evaluate the success rate, complications, and long-term prognosis of redo CRT implantation, including the rates of subclavian, cava, and coronary sinus (CS) vein thrombosis as well as re-infection. Methods and results: Between 2007 and 2014, 1712 lead extractions were performed in 537 patients with device-related infection at Heart Center Brandenburg. Of the 537 patients, 125 (23%) underwent CRT device and lead extraction, including extraction of the left ventricular lead from the coronary sinus. Of these 125, 62 (50%) patients underwent redo CRT implantation (mean age, 68 ± 10 years); 34 patients had coronary artery disease (CAD) while 28 had dilated cardiomyopathy (DCM). The mean left ventricular ejection fraction was 27% ± 7%. The mean QRS duration of the left bundle branch block was 158 (range, 147–162) ms, and 25 patients had atrial fibrillation (AF). All these patients were followed up for a median duration of 29.6 (range, 15–43) months. In 53 of the 62 patients (85%), the CRT system was successfully re-implanted; however, the original CS vein could be used again only in 28 (45%) patients. The all-cause mortality rate was 7.1% after 1 year, and it was significantly higher in patients whose N-terminal pro B-type natriuretic peptide level was ≥3, 000 pg/mL ( P < 0.001), those who were aged ≥64 years ( P = 0.028), those who had CAD ( P = 0.042) or chronic kidney insufficiency ( P = 0.001), those with AF ( P = 0.001) and those whose blood cultures were positive for Staphylococcus aureus ( P = 0.014). Conclusion: Redo CRT implantation after device extraction owing to device-related infection has a low success rate and shows a higher rate of re-infection than that observed in patients who undergo CRT implantation for the first time. Further, patients whose blood cultures are positive for S . aureus show a particularly poor outcome.